Dental caries and oral hygiene in patients treated at the Clinica del Niño of Faculty Dentistry at San Marcos University - Castañeda Mosto, Maria (2009)
The aim of the present study was to assess the prevalence of dental caries and the stateof the oral hygiene in pediatric patients who received dental care at the Clínica del Niño, of Faculty Dentistry. The type of the investigation was descriptive with a sample of 399 patients whose parents authorized the permission for the investigation. The patients of the study were, medical conditions compromised, handicapped children, complex children, children no receptive, children with orthodontics problems, children with urgency problems, and bbies. First we collected the personal datum and then it was collected the clinical examination, using the dental index for DMFT, dmft and the simplified index hygiene of Green and Vermillion. The results obtain were a average of 3,57 for dental caries of all the samples and the 91,18 % had an oral hygiene index from regular to bad. The highest results of the dmft index were for complex children 7,89 and for DMFT index was to the handicapped children 5,17. The babies show a dmft index of 2,26.The investigation concludes that the majority of patients were a high prevalence of dental caries and a poor oral hygiene.